2014
DOI: 10.14434/jotlt.v3n2.12872
|View full text |Cite
|
Sign up to set email alerts
|

Using E-Book annotations to develop deep reading

Abstract: This quick hit describes strategies for modeling and assessing critical reading in an e-textbook environment at the collegiate level over the course of a single semester.  Special attention is devoted to annotation practices associated with critical reading: outlining, connecting, questioning, and objecting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…A review of our results offers support for many but not all of our current hypotheses, and provides support for our earlier preliminary conclusions (Jensen & Scharff, 2014) that critical reading is challenging to develop, that a course design that pervasively incorporates development of annotation skills using an e-text is effective, and that practice using an e-text and its annotation features can lead to significant positive shifts in attitudes about e-texts.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A review of our results offers support for many but not all of our current hypotheses, and provides support for our earlier preliminary conclusions (Jensen & Scharff, 2014) that critical reading is challenging to develop, that a course design that pervasively incorporates development of annotation skills using an e-text is effective, and that practice using an e-text and its annotation features can lead to significant positive shifts in attitudes about e-texts.…”
Section: Discussionsupporting
confidence: 73%
“…However, we also believe that in order for students to make progress in the development of their critical reading skills in an electronic environment, they must do it themselves. Based on our earlier work (Jensen & Scharff, 2014), we also believe that they must be intentionally taught how to do this. In other words, we believe that instructors must teach students how to make use of electronic tools for critical reading in order for students make learning gains.…”
mentioning
confidence: 99%
“…Yet another study found that tools or features promoting self-reflection among students lead to better learning outcomes in chemistry, language learning, physics and math problem-solving (Means et al, 2009 ). Jensen and Scharff ( 2014 ) highlights the need for incorporating multiple opportunities for practice and feedback so as to develop critical reading skills among learners through eBook readers. Lin et al ( 2017 ) have reported on how to appropriately shape the instructional design of online lecture videos to effectively engage learners.…”
Section: Foundationsmentioning
confidence: 99%
“…The researchers found that annotations had a positive effect on inference-level questions in the print condition only, and had no impact on factual level questions in either medium. The role of annotation in supporting critical reading alone, or, in addition, how critical reading then translates into critical writing, has also been studied (e.g., Jensen and Scharff 2014;Liu 2006), with one study finding that "skillful annotators produced more critical and analytical writing samples than did verbatim annotators. Verbatim annotators recycled information rather than analyzing it" (Liu 2006, p. 205).…”
Section: Literature Reviewmentioning
confidence: 99%